New e-Health Tracks in Engineering Education of the Politecnico di Milano - Pinciroli, F.; Masseroli, M.; Bonacina, S. (Yearbook of Medical Informatics, 2005)
In Italian universities, most curricula have recently been deeply innovated. Out of the historical and usual five-year-based degrees to be taken after the five-year-based Secondary School / High School the University system moved into a 3+2 year university framework. Engineering curricula were changed too. Such a wide reform forced the redesign of many courses, even entire course tracks. In some cases it also facilitated the re-design of Doctoral (Ph.D.) programs. The introduction of some one-year based and subject-focused programs, to be taken right after a specifically considered degree, was facilitated as well.At the Engineering Faculties of the Politecnico di Milano, as far as it concerns Medical Informatics and Telemedicine, curricular courses and course tracks, as well as a couple of one-year subject-oriented programs have been widely re-organized. We describe the entire new educational offer.The aim of the educational offer remains to enable students to acquire technical skills, and to use them for becoming Medical Information and Communication Technology experts. Often the student involvement in research is the practical pass for obtaining such result. In doing so students understand better what a positive technological return for the users is. Running research programs relate to the Visible Human Dataset and Digital Anatomy, to textual and image Data Integration, to Health Information System and eHealth, and to Bioinformatics. Some prototypes, developed at the Laboratory of Medical Informatics and Telemedicine, are briefly mentioned.